Problematika Manajerial dan Kurikulum Pesantren - Fatoni, Mahfud Heru; Anshory, Isa (TSAQOFAH, 2024)
The education system that first appeared in Indonesia was the Islamic boarding school. In its development, Islamic boarding schools have always innovated and transformed themselves, both in terms of the content (material) taught and in terms of methods and management. However, the reality on the ground is that there are still many problems faced by Islamic boarding schools. This research aims to explore managerial problems and Islamic boarding school curriculum. In this research, library research or qualitative methods are used which refer to books and previous research. The results of the research show that Islamic boarding school managerial problems include Islamic boarding school policies being under the authority of the Kyai, the condition of students in terms of clothing, health and behavior as well as the "all mono" administrative pattern. Meanwhile, curriculum problems include providing general lessons that are less effective and a passive learning atmosphere. In conclusion, the development of science and technology creates increasingly high demands on Islamic boarding school educational standards so it is necessary to develop strategies to increase the progress of Islamic boarding schools that promise guarantees of knowledge, personality and skills.